Exploring the Verb Agreement System in the Lohorung Language - Rai, Diwas (Journal of Indigenous Knowledge and Practice, 2025)
This article analyzes the verb agreement system in Lohorung, a Kirat Rai language belonging to the Tibeto-Burman family. Using elicitation methods with a native speaker and textual analysis, we find that Lohorung verbs exhibit simultaneous agreement with both subject and object pronouns, marked by <-ŋ>, <-nɑ>, <-u>, <- sti>, <-i> and <-kɑ>. The key findings reveal that: (a) present tense verbs with unmarked ergative subjects show single agreement, (b) clusivity is marked exclusively (inclusive forms remain unmarked), and (c) agreement undergoes assimilation (e.g., portmanteau<-u> for third person singular past. Notably, the system does not show gender or honorific distinctions. These results demonstrate Lohorung’s complex yet rule-governed agreement morphology, contributing to Tibeto-Burman typology and endangered language documentation.